Analisis Peningkatan Performa Akses Website dengan Web Server Stress Tool - Hendra Kurniawan; Eka Puji Widiyanto (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2016)
Website access speed is marked with a fast loading time duration and reliability of the web server has a significant effect in providing comfort for the user when accessing the website. The stability is very dependent on the access to the website owned by the web server performance as well as the large size of the page. The scope of the issues examined included the testing and selection of web servers that are reliable and the implementation of the action optimization of web templates include Image Compression, Browser Cache, Minify CSS, HTML and Javascript files, Anti Render-Blocking Javascript placement CSS stylesheets, script placement Javascript. Stability testing of web servers and website access speed is measured via Web Server Stress Tool application version 8 with the type of test that has the RAMP test and parameter included Users Simultaneous, Click, Error, Error (%) Avg. Click Times (ms), and Time Spent (ms). Research methodology oriented to the analysis of the reliability of the web server and web access speed comparison test between the data pre-test and post-test web test results of the implementation of the optimization of the web template. Based on the results of the discussion is concluded that the obtained web server owned dracoola.com have the best quality and performance so it supports the stability of the web. In addition, it can also be concluded that there is increased access speed or loading time amounted to 43.19% (avg. Click times) and 32.80% (time spent) after implementing optimization measures on web templates.